Software tool for horizontal-axis wind turbine simulation - Vitale, Alejandro José (2008)
The main problem of a wind turbine generator design project is the design of the right blades capable of satisfying the specific energy requirement of an electric system with optimum performance. Once the blade has been designed for optimum operation at a particular rotor angular speed, it is necessary to determine the overall performance of the rotor under the range of wind speed that it will encounter. A software tool that simulates low-power, horizontal-axis wind turbines was developed for this purpose. With this program, the user can calculate the rotor power output for any combination of wind and rotor speeds, with definite blade shape and airfoil characteristics. The software also provides information about distribution of forces along the blade span, for different operational conditions.